3D-printed Drugs: A Fabrication of Pharmaceuticals towards Personalized Medicine - Haris, Muhammad Salahuddin; Azlan, Nur Hakimah Mohd; Taher, Muhammad; Rus, Shaiqah Mohd; Chatterjee, Bappaditya (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Three-dimensional (3D) printing fabricates a structure by depositing materials layer-by-layer to form an object. Drug personalization receives attention due to problems arising from drug treatments such as undesirable side effects and ineffective drug therapy among pediatric and geriatric patients. Hypothesis: Conventional dosage form faces issues such as non-adherence to medication, ineffective treatment due to non-preferable dosage form and non-optimized drug release. Personalized 3D printing drugs offer personalized drug dosing, novel drug release profile and unique dosage form production. Results and Conclusion: Therefore, this review discussed the benefits of 3D-printed drugs and an overview of the standard 3D printer technology used in pharmaceuticals. This article aimed to review the current application of 3D-printed drugs in the personalization of drug dosing, the variation of drug release profile and fabrication of unique drug dosage form. Further research and experimentation of 3D-printed drugs are recommended as they will offer a significant aid in the customization of medicine. The potential utilization of 3D-printed drugs in optimizing effective and safe medication is undeniable. However, there are some challenges needed to be overcome, such as compatibility between chosen methods with materials used, difficulty to scale-up production, regulatory requirement as well as protection of individual rights issues.
Keywords: 3D-printed drugs; Personalized dosing; 3D printer; Polypills; Patient; compliance; Drug release profile